Effectiveness of an online self‐help program, expert‐patient support, and their combination for eating disorders: Results from a randomized controlled trial. Issue 10 (30th July 2022) - Rohrbach, Pieter J.; Dingemans, Alexandra E.; Spinhoven, Philip; Van Ginkel, Joost R.; Fokkema, Marjolein; Wilderjans, Tom F.; Bauer, Stephanie; Van Furth, Eric F.
Abstract: Objective: Many individuals with an eating disorder do not receive appropriate care. Low‐threshold interventions could help bridge this treatment gap. The study aim was to evaluate the effectiveness of Featback, a fully automated online self‐help intervention, online expert‐patient support and their combination. Method: A randomized controlled trial with a 12‐month follow‐up period was conducted. Participants aged 16 or older with at least mild eating disorder symptoms were randomized to four conditions: (1) Featback, a fully automated online self‐help intervention, (2) chat or email support from a recovered expert patient, (3) Featback with expert‐patient support and (4) a waiting list control condition. The intervention period was 8 weeks and there was a total of six online assessments. The main outcome constituted reduction of eating disorder symptoms over time. Results: Three hundred fifty five participants, of whom 43% had never received eating disorder treatment, were randomized. The three active interventions were superior to a waitlist in reducing eating disorder symptoms ( d  = −0.38), with no significant difference in effectiveness between the three interventions. Participants in conditions with expert‐patient support were more satisfied with the intervention. Discussion: Internet‐based self‐help, expert‐patient support and their combination were effective in reducing eating disorder symptoms compared to a waiting list control condition. Guidance improved satisfaction with the internet intervention but not its effectiveness. Low‐threshold interventions such as Featback and expert‐patient support can reduce eating disorder symptoms and reach the large group of underserved individuals, complementing existing forms of eating disorder treatment. Public significance statement: Individuals with eating‐related problems who received (1) a fully automated internet‐based intervention, (2) chat and e‐mail support by a recovered individual or (3) their combination, experienced stronger reductions in eating disorder symptoms than those who received (4) usual care. Such brief and easy‐access interventions play an important role in reaching individuals who are currently not reached by other forms of treatment.